PREVALENCE OF GERIATRIC DISEASES AMONG PARENTS OF MEDICAL DOCTORS IN LAHORE - Khan, Muhammad Athar; Mushtaq, Muhammad; Ahmad, Muhammad Zameer; Amir, Hena; Bajwa, Tariq Mahmood; Laeeque, Shaikh Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
Background: The burden of geriatric diseases has a significant impact upon the socio-cultural, socioeconomic and administration of health services. The study was carried out to identify a burden of geriatric conditions, magnitude of disease problems and involvements of body systems in the parents of medical doctors from Lahore. Methods: After taking the consent, interview based active disease surveillance/information was collected from a total of 137 medical doctors and their parents. They were interviewed about the health status of their parents and recorded in a pre-tested questionnaire. The prevalence of each system involved in each of the category of parents was compared by ANOVA at a significant alpha level of 0.05. Results: Prevalence of cardiovascular diseases was the highest, (18.61%), followed by musculoskeletal (10.21%) and digestive system (9.12%). The ranking of other systems in descending order was 4.74%, 3.64% and 1.82% for the respiratory system, urogenital system, and ENT respectively due to single system involvement. A cumulative prevalence due to all diseases in terms of disease load/burden of diseases in both mothers and fathers was 53.28% due to single system involvement and 67.51% because of multiple system involvement. Conclusion: Fiftythree percent of the older population, who were above the age of 60, were sick due to the involvement of one body system and sixty eight percent had multiple body systems involvement. Keywords Geriatrics, Morbidity, Prevalence, Ranking order, Burden, Pakistan